Valor nutritivo da raiz e folhas da mandioca para a tilápia do Nilo - de Carvalho, Pedro Luiz Pucci Figueiredo [UNESP]; da Silva, Rafael Lopes [UNESP]; Botelho, Renan de Mattos [UNESP]; Damasceno, Flávia Mota [UNESP]; Rocha, Mariucha Karina Honório Ribeiro [UNESP]; Pezzato, Luiz Edivaldo [UNESP] (My University, 2012)
The aim was to evaluate the nutritional value of the root and leaves of cassava (Manihot sculenta) for juveniles of Nile tilapia (Oreochromis niloticus). Three diets were prepared, a reference and two test diets. The first tested diet contained 50.0% of cassava root and 50.0% of reference diet and the second one consisted of 30.0% of cassava leaf meal and 70.0% of reference diet. Moreover, in every diet was added 0.1% chromium oxide-III (Cr2O3) as inert marker. Sixty juveniles (100.0 ± 9.0 g) were accommodated in cages (10 fish/cage) for feeding and feces collection. During the day these cages were maintained in a feeding tank (250 L), one tank for each treatment, where they were fed until apparent satiation. After the aforementioned feeding period they were transferred to a fecal collection tank, where they remained until next morning. The collected feces were frozen and dried for analyzes. The apparent digestibility coefficients (ADC) were calculated on basis of Cr2O3 concentration present in diets and feces. The ADC of reference diet for DM, cassava leaf and root were, respectively 85.23%, 81.22% and 91.44%; CP to 97.35%, 73.37% and 91.46% and for the GE to 87.70%, 64.70% and 92.20%, the values obtained for the diet with cassava root significantly higher (P<0.05). Summarizing, root and cassava leaves can be used as alternative ingredients for compose balanced diets for Nile tilapia juveniles.
Nutritional value of root and leaves of cassava for Nile tilapia
Keywords: Apparent digestibility; Fish nutrition; Manihot sculenta; Oreochromis niloticus